Desenvolvimento de um controlador híbrido Fuzzy-PID para estabilização de um VANT do tipo quadrirrotor na realização de um voo autônomo vertical - Morais, Edpo Rodrigues de (Brasil, 2017)
This dissertation proposes the development of a Fuzzy-PID hybrid controller for the height stability control of a four-engine type UAV. The work also contemplates the development of a classical PID controller, used to compare with the hybrid one purposed. The AuRoRA platform is used for the realization of tests with both of the control structures, being this one provided with the parameters of the Drone used. With the test results, it was possible to conclude that both of the controllers, the classical PID and the Fuzzy-PID, are able to perform the Drone height control, and the hybrid control obtained some advantages such as the ability of self-adjust with the system variation, that dispenses the manual tuning of the gains, besides presenting an improvement in the Drone height stability
Keywords: Quadrirrotor; Controle híbrido Fuzzy-PID; Controle PID; Voo vertical; Estabilização de altura; Four-wheel drive; Fuzzy-PID hybrid controller; PID control; Vertical flight; Height stabilization; ENGENHARIAS::ENGENHARIA ELETRICA